Use of butorphanol as a local anaesthetic for pain management in calves undergoing umbilical hernia repair - Interlandi, Claudia; Spadola, Filippo; Neve, Veronica C.; Tabbì, Marco; Di Pietro, Simona; Giudice, Elisabetta; Macrì, Daniele; Costa, Giovanna L. (Frontiers in Veterinary Science, 2024)
The aim of the study was to compare the analgesic efficacy of butorphanol and lidocaine, alone or in combination, in calves undergoing surgical repair of umbilical hernia. The study was conducted in 60 calves of different breeds. Xylazine 0.3 mg/kg was administered intramuscularly to all animals in the study. The animals were then divided into three groups (n = 20) that received different treatments with lidocaine at 4.5 mg/kg and butorphanol at 0.02 mg/kg. The L group received lidocaine both by infiltration of the surgical planes and intraperitoneally, the B group received butorphanol both by infiltration of the surgical planes and intraperitoneally, and finally the LB group received lidocaine by infiltration of the surgical planes and butorphanol intraperitoneally. Heart and respiratory rates, haemoglobin oxygen saturation, non-invasive blood pressure and temperature were recorded during surgery. Response to the surgical stimulus was scored on a cumulative numerical scale that included percentage changes in HR, RR and SAP. Postoperative pain was assessed by three independent observers, blinded to treatment, using the UNESP-Botucatu Unidimensional Composite Pain Scale (UNESP-Botucatu UCPS-IV) for the assessment of postoperative pain in cattle. The course of physiological variables was appropriate for patients under anaesthesia. No subject required rescue intraoperative analgesia. In group L, 4 subjects at 40 m and 5 subjects at 50 m required postoperative rescue analgesia. Both butorphanol alone and the combination of butorphanol and lidocaine showed excellent intraoperative and postoperative scores. Furthermore, this combination did not cause any cardiopulmonary or other adverse effects. Based on the results of this study, both butorphanol alone and the co-administration of butorphanol and lidocaine administered locally proved to be safe and effective in providing adequate and long-lasting analgesia in calves, helping to reduce postoperative discomfort and maintaining adequate animal welfare.